Congenital smooth muscle hamartoma/Post-vaccination hypertrichotic granuloma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2022)
Congenital smooth muscle hamartoma and hypertrichotic granuloma secondary to vaccination are two very different conditions that share localized hypertrichosis. Moreover, they come to observation in the first months of life, thus requiring a differential diagnosis.